Needs for rehabilitation in China: Estimates based on the Global Burden of Disease Study 1990–2019 - Tian Tian; Lin Zhu; Qingzhen Fu; Shiheng Tan; Yukun Cao; Ding Zhang; Mingxue Wang; Ting Zheng; Lijing Gao; Daria Volontovich; Yongchen Wang; Jinming Zhang; et al. (Chinese Medical Journal)
Abstract. Background:. As an essential part of health services, rehabilitation is of great significance to improve the health and quality of life of the whole population. Accelerating aging calls for a significant expansion of rehabilitation services in China, but rehabilitation needs remain unclear. We conducted the study to explore the rehabilitation needs in China and project the trend of rehabilitation needs from 2020 to 2034. Methods:. The data of health conditions that might potentially benefit from rehabilitation were obtained from Global Burden of Disease (GBD) study. Estimated annual percentage changes (EAPCs) were calculated to quantify the trends of the age-standardized rates. Projections of rehabilitation needs were made until 2034 using Bayesian age–period–cohort analysis (BAPC). Results:. Approximately 460 million persons (33.3% of the total population) need rehabilitation in China, contributing to 63 million years lived with disabilities (YLDs) in 2019. The number of prevalent cases that need rehabilitation increased from around 268 (95% uncertainty interval [UI]: 257–282) million in 1990 to almost 460 (95% UI: 443–479) million in 2019, representing an increase of 71.3%. The highest contribution to the need for rehabilitation was musculoskeletal disorders with about 322 (95% UI: 302–343) million persons in seven aggregate disease and injury categories, and hearing loss with over 95 (95% UI: 84–107) million people among 25 health conditions. Based on the projection results, there will be almost 636 million people (45% of the total population) needing rehabilitation services in China by 2034, representing an increase of 38.3%. The rehabilitation needs of neoplasms, cardiovascular diseases, and neurological disorders are expected to increase significantly from 2019 to 2034, with increases of 102.3%, 88.8% and 73.2%, respectively. Conclusions:. The need for rehabilitation in China substantially increased over the last 30 years. It is predicted that over two in five people will require rehabilitation by 2034, thus suggesting the need to develop rehabilitation services that meet individuals’ rehabilitation needs.